(untitled) (Annals of Medical Research, 2021)
Aim: Brucellosis is a zoonotic infection caused by bacteria of the genus Brucella. The disease causes genitourinary system involvement and abortion, which is the most critical complication of the disease, in cattle. Although it is known to cause spontaneous abortion, preterm birth and intrauterine death in humans, the number of systematic studies on the subject is limited. This study compared the patients who experienced pregnancy loss and women who carried their pregnancy to term without any problems in terms of serology for brucellosis in our region which is an endemic region. Materials and Methods: The study was conducted in the Clinic of the Department of Obstetrics and Gynecology in Gaziantep University Hospital between August 2012-June 2013. The study was conducted with 71 patients who experienced intrauterine pregnancy loss and 109 women who carried their pregnancy to term without any problems as the control group, wherein all subjects were aged between 18 and 40. These two groups were in a similar age group and had a similar gestational age. Results: There were 4 (5,6%) subjects who were brucella-positive in the patient group and 1 (0,9%) subjects who were brucella- positive in the control group according to the serology for brucellosis. C-reactive protein, erythrocyte sedimentation rate, aspartate aminotransferase, abortus, and parity were significantly high in women who experienced pregnancy loss (p<0.05). The rate of living in rural areas as well as the frequency of fever, chills, shivering and lower back pain was significantly high in the patient group. When the patient group was divided into two subgroups according to the serology for brucella, patients with positive serology had a significantly higher rate of joint pain and animal contact (livestock farming) history. Although there was no significant relationship between brucella agglutination titration and pregnancy loss, the number of the brucellosis patients and agglutination titrations were higher particularly in the group of women who experienced pregnancy loss. Conclusion: Prospective studies that will be conducted with larger patient groups are required to better reveal the relationship between pregnancy and brucellosis. Moreover, serology for brucella can be used as a screening method to provide early treatment and prevent complications associated with brucellosis during pregnancy follow-up especially in endemic region.